2021
DOI: 10.1186/s12906-021-03399-8
|View full text |Cite
|
Sign up to set email alerts
|

Topical gel based nanoparticles for the controlled release of oleanolic acid: design and in vivo characterization of a cubic liquid crystalline anti-inflammatory drug

Abstract: Background Oleanolic acid (OA) has multiple pharmaceutical applications including anti-inflammatory activity, but low permeability of the molecule limits its widespread use. Methods A cubic liquid crystalline nanoparticle (LCNP)-based gel was prepared as a potential topical delivery system for OA. The LCNP-based gel was optimized using rheological, drug release kinetic, and ex vivo permeation studies. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In vitro drug release study data were fitted to different models such as zero order and first order equations to predict the kinetics and drug release mechanism. The release profile of curcumin from the nanocrystal gel was found to follow first order kinetics (R 2 = 0.9908) based on a greater regression coefficient value as compared to that of the zeroorder model (R 2 = 0.9041) [45].…”
Section: Kinetic Analysis Of In Vitro Drug Release Studiesmentioning
confidence: 93%
See 1 more Smart Citation
“…In vitro drug release study data were fitted to different models such as zero order and first order equations to predict the kinetics and drug release mechanism. The release profile of curcumin from the nanocrystal gel was found to follow first order kinetics (R 2 = 0.9908) based on a greater regression coefficient value as compared to that of the zeroorder model (R 2 = 0.9041) [45].…”
Section: Kinetic Analysis Of In Vitro Drug Release Studiesmentioning
confidence: 93%
“…This faster wound contraction and healing in this treatment group was due to the rapid solubilizing effect of curcumin crystals and permeation into the tissues. The nanosize of the crystals was responsible for their rapid dissolution in the gel base, which would not have been possible for the relatively larger particle size of the plain curcumin powder (FC-1) [45] It was observed that the rate of wound healing was also significant (p < 0.05) in Group IV when compared to Group I and II for the same reason. As expected, using a higher strength of curcumin nanocrystals of 1.0% w/w in gel also made a difference to the percentage of wound contraction when comparing Group V to Group IV which received 0.5% w/w.…”
Section: Excision Wound Healing Studymentioning
confidence: 99%
“…The Peppas equation suggested non-Fickian diffusion, implying multiple controlled release processes. The OA-loaded LCNP gel exhibited efficacy in a rodent inflammation model, providing sustained relief after a single application [ 156 ]. Efforts were made to enhance the solubility of OA and UA also using polyurethane nanostructures (PU) synthesized through interfacial polycondensation and spontaneous emulsification.…”
Section: Challenges In Oa Deliverymentioning
confidence: 99%
“…Various delivery forms have been previously used for nanoparticles, including directly applying the NPs dispersed in water, saline, or PBS [21] and semi-solid formulations. There are several examples of NPs formulated in an acrylate gel based on Carbopol ® ETD 2020 [14] or Carbopol ® 934 [22], hydroxypropyl methylcellulose (HPMC) [23,24], Xanthan gum [25], Poloxamer 407 [26], and colloidal silica [27]. For the LSN systems, the use of polysaccharide thickeners such as xanthan gum or modified celluloses (e.g., hydroxypropyl cellulose, hydroxyethyl cellulose, or carboxymethyl cellulose) were not utilized since these linear fiber-based polymers may hinder permeation of the nanoparticles.…”
Section: Formulation Developmentmentioning
confidence: 99%